2003
DOI: 10.1017/s1752756200012850
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maturity of maize silage at harvest on the performance of lactating dairy cows offered three contrasting grass silages

Abstract: Recent developments in maize breeding and in agronomic practices, particularly the development of degradable full cover plastic mulch, have resulted in the possibility of consistently producing high yields of high starch maize silage in Northern Ireland. However, there is considerable variability in the quality of maize and grass silages produced. In a recent study Keady et al. (2002) concluded that the highest yield of fat and protein from dairy cows was obtained from maize silage ensiled at approximately 30%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Improvements in intakes with inclusion of MS in GS-based diets have been demonstrated in previous studies with beef cattle (Browne et al, 2000;O'Kiely and Moloney, 2000) and with dairy cows (Phipps et al, 1995O'Mara et al, 1998;Keady et al, 2002aKeady et al, , 2003.…”
Section: Total Diet Dm and Me Intakementioning
confidence: 69%
“…Improvements in intakes with inclusion of MS in GS-based diets have been demonstrated in previous studies with beef cattle (Browne et al, 2000;O'Kiely and Moloney, 2000) and with dairy cows (Phipps et al, 1995O'Mara et al, 1998;Keady et al, 2002aKeady et al, , 2003.…”
Section: Total Diet Dm and Me Intakementioning
confidence: 69%
“…Whilst many studies have shown that including maize silage in the forage component of diets offered to beef cattle and dairy cows increases animal performance (Keady 2005, 2008a few studies have been undertaken to evaluate the effects on the performance of pregnant ewes or finishing lambs. One of the characteristics of maize silage is its low crude protein concentration (consistently less than 100 g (kg DM) -1 , which declines as maturity increases (Keady et al 2003(Keady et al , 2008a and may impact on its ability to meet the protein requirements of ewes in early and mid pregnancy. Robinson (1983) concluded that forages offered during early and mid pregnancy should contain a minimum crude protein concentration of 10 g per MJ of ME, otherwise the forage needs to be supplemented with protein to meet requirements.…”
Section: Effects Of Maize On Performance Of Pregnant Ewesmentioning
confidence: 99%
“…Previously, Keady et al (2008a) observed, with dairy cows, that partially (40%) replacing medium FV and high FV grass silages with maize silage resulted in total daily DMI increases of 2.25 and 0.51 kg/cow, respectively. Similarly, Keady et al (2003) observed that, with grass silages of low (ME 10.2 MJ/ kg DM), medium (ME 11.0 MJ/kg DM) and high (ME 12.0 MJ/ kg DM) FV, replacing of 40% of the grass silage with maize silage resulted in a response in daily total DMI of +1.85, +1.45 and −0.10 kg/cow, respectively. The response to concentrate feed level in late pregnancy is dependent on forage FV, and thus a substitution effect.…”
Section: Developments In Nutrition Of Sheepmentioning
confidence: 70%
“…Using a precision chop harvester relative to single chopping to reduce chop length increased silage intake and, consequently lamb BW by 0.25 kg whilst reducing ewe weight loss during pregnancy by 4.9 kg (Chestnutt, 1989). Increasing the DM concentration of maize at harvest alters chemical composition of the resulting silage, due to reduced concentrations of acid detergent fibre and CP, and increases starch and ME concentrations (Keady et al, 2003(Keady et al, , 2008a. Increasing the DM of maize at harvest (DM from 180 to 259 g/kg) offered to ewes during mid and late pregnancy increased total DM and ME intakes by 31% and 43%, respectively, and ewes were 4.2 kg heavier at lambing and had a significantly higher BCS, but lamb BW was not altered (Keady & Hanrahan, 2021), indicating partitioning of ME to BCS rather than to foetal growth.…”
Section: Developments In Nutrition Of Sheepmentioning
confidence: 99%
See 1 more Smart Citation